2013
DOI: 10.1001/jamapediatrics.2013.2356
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Habits, Happy Homes

Abstract: clinicaltrials.gov Identifier: NCT01565161.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
163
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(166 citation statements)
references
References 43 publications
2
163
0
1
Order By: Relevance
“…Because sleep habits and routines may persist from childhood into adulthood, it is important to focus on sleep routines in early childhood as a potentially effective obesity intervention strategy. As Haines et al (2013) demonstrated, interventions targeting child sleep duration can effectively influence positive and protective behavior change. Future studies should continue to focus on understanding how both child and adult sleep routines relate to obesity and health outcomes, and which mechanisms affect how and when sleep routines provide the most beneficial influence on obesity and health outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because sleep habits and routines may persist from childhood into adulthood, it is important to focus on sleep routines in early childhood as a potentially effective obesity intervention strategy. As Haines et al (2013) demonstrated, interventions targeting child sleep duration can effectively influence positive and protective behavior change. Future studies should continue to focus on understanding how both child and adult sleep routines relate to obesity and health outcomes, and which mechanisms affect how and when sleep routines provide the most beneficial influence on obesity and health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the focus on risks and negative factors that increase prevalence of obesity (such as cumulative risk models), some researchers have focused on examining positive routines that act as protective factors to decrease prevalence of obesity (e.g., Anderson and Whitaker, 2010; Haines et al, 2013). These researchers have focused on the potential of promoting positive health-related behaviors and daily routines as positive mechanisms of change relating to obesity and health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of routines has been shown to be helpful in improving obesogenic behaviors and reducing weight [69]. FBT focuses on the establishment of routines for eating, physical activity, and sleep.…”
Section: Fbt Treatment Componentsmentioning
confidence: 99%
“…children's BMIs by helping their families make small, no-cost changes in basic home routines 7 . In her "Healthy Habits, Happy Homes" study, Taveras and her colleagues dispatched health coaches to work with low-income families with children between the ages of 2 and 5.…”
Section: Measuring Weights How Do We Define Obesity?mentioning
confidence: 99%